Towards Technical Fluency: Assessing the English Language Needs of Mechanical Engineering Students in a University ESP Context - Zulfahmi, Muhammad Riko Yohansyah; Kardena, Absharini (CV. ITTC INDONESIA, 2024)
This study investigates the English language needs of Mechanical Engineering students in a university ESP class. Through a questionnaire distributed to 21 students, the findings reveal that 81% recognize the crucial role of English proficiency in their academic and professional pursuits. Specific language skills such as vocabulary and grammar practice are considered important, emphasizing the overall significance of language proficiency. The research underscores the importance of reading tasks, with technical documents, textbooks, and instructions deemed essential. However, a lack of emphasis on oral communication skills is evident, as tasks related to speaking are generally considered non-essential by the majority of students. While specific listening skills in certain contexts are valued, the study also points to a need for curriculum development in oral communication. Writing tasks, particularly SOPs and technical reports, are highly valued, but other forms of writing receive less emphasis. The study provides valuable insights into the linguistic needs of Mechanical Engineering students, offering guidance for curriculum development and instructional strategies to enhance their language skills for academic and professional success.